2022
DOI: 10.3389/fcvm.2022.1022183
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of COVID-19 infection in congenital heart disease: A single-center experience in Indonesia

Abstract: BackgroundCongenital heart disease (CHD) patients are thought to be vulnerable to COVID-19 complications. In this study, we would like to assess the outcomes and clinical characteristics in COVID-19 CHD patients.MethodA single-center, observational study was conducted in National Cardiovascular Center Harapan Kita (NCCHK). This study included patients with CHD who were hospitalized for COVID-19. The extracted data were baseline characteristics, clinical findings, supportive examination findings, complications,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
2
1
Order By: Relevance
“…Another interesting nding in this study was the recurrence of SARS-CoV-2 after surgeries, which was not reported by previous CHD reports [16,17,21,22]. The recurrence rate was as high as 20% (8/40), and all recurrences were detected by re-positive nucleic acid tests on the day of surgery after patients were admitted to the ICU.…”
Section: Discussioncontrasting
confidence: 43%
“…Another interesting nding in this study was the recurrence of SARS-CoV-2 after surgeries, which was not reported by previous CHD reports [16,17,21,22]. The recurrence rate was as high as 20% (8/40), and all recurrences were detected by re-positive nucleic acid tests on the day of surgery after patients were admitted to the ICU.…”
Section: Discussioncontrasting
confidence: 43%
“…Congenital heart disease (CHD) is prevalent in 1% of the population [ 20 ]. These children are at increased risk for complications from respiratory viral infections, including influenza and respiratory syncytial virus (RSV) [ 21 , 22 ], but there are only limited data on complications associated with COVID-19 infection among children with CHD [ 2 , 23 , 24 ]. Here, we report an analysis from a recent nationwide cross-sectional retrospective study based on the United States National Inpatient Sample (NIS) database to examine mortality risks and in-hospital cardiovascular and non-cardiovascular complications as a result of COVID-19 infection among children with CHD.…”
Section: Introductionmentioning
confidence: 99%
“…[20] These children are at increased risk for complications from respiratory viral infections, including in uenza and respiratory syncytial virus (RSV) [21,22], but there are only limited data on complications associated with COVID-19 infection among children with CHD. [2,23,24] Here, we report an analysis from a recent nationwide cross-sectional retrospective study based on the United States National Inpatient Sample (NIS) database to examine mortality risks and in-hospital cardiovascular and non-cardiovascular complications as a result of COVID-19 infection among children with CHD.…”
mentioning
confidence: 99%